The Pengaruh Penerapan Model Pembelajaran Index Card Match terhadap Hasil Belajar Siswa dalam Pembelajaran Geografi di SMA Laboratorium Undiksha - Piscesita, Brilliantari Boeky; Astawa, Ida Bagus Made; Wesnawa, I Gede Astra (Universitas Pendidikan Ganesha, 2025)
The designs of our research are to analyze the utilization of the Index Card Match learning model in high school geography learning, analyze student learning outcomes before and after the application of the Index Card Match learning model in geography learning in high school, analyze the effect of the Index learning model Card Match in geography learning on student learning outcomes in high school, and highlights the obstacles faced by teachers in implementing the Index Card Match learning model in geography learning in high school. This study used an experiment with the Non-equivalent Control Group Design with the observation and tests Method. The outcomes declared that The Index Card Match Learning Model in geography learning at SMAS Laboratory Undiksha can apply teachers in the